2017
DOI: 10.7150/thno.19883
|View full text |Cite
|
Sign up to set email alerts
|

PET Tracer 18F-Fluciclovine Can Detect Histologically Proven Bone Metastatic Lesions: A Preclinical Study in Rat Osteolytic and Osteoblastic Bone Metastasis Models

Abstract: 18F-Fluciclovine (trans-1-amino-3-18F-fluorocyclobutanecarboxylic acid; anti-18F-FACBC) is a positron emission tomography (PET) tracer for diagnosing cancers (e.g., prostate and breast cancer). The most frequent metastatic organ of these cancers is bone. Fluciclovine-PET can visualize bony lesions in clinical practice; however, such lesions have not been described histologically.Methods: We investigated the potential of 14C-fluciclovine in aiding the visualization of osteolytic and osteoblastic bone metastases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The article in this issue entitled “PET Tracer 18 F-Fluciclovine Can Detect Histologically Proven Bone Metastatic Lesions: A Preclinical Study in Rat Osteolytic and Osteoblastic Bone Metastasis Models” by Oka et al . 2 expands our insight into the bone metastatic niche and how it interacts with targeted radionuclides. This article provides novel information describing the histological characteristics of bone metastasis and how this relates to the uptake of the radiotracers- fluciclovine, fluorodeoxyglucose (FDG), choline and hydroxymethylene diphosphonate (HMDP), that have not been previously examined in the literature.…”
mentioning
confidence: 86%
“…The article in this issue entitled “PET Tracer 18 F-Fluciclovine Can Detect Histologically Proven Bone Metastatic Lesions: A Preclinical Study in Rat Osteolytic and Osteoblastic Bone Metastasis Models” by Oka et al . 2 expands our insight into the bone metastatic niche and how it interacts with targeted radionuclides. This article provides novel information describing the histological characteristics of bone metastasis and how this relates to the uptake of the radiotracers- fluciclovine, fluorodeoxyglucose (FDG), choline and hydroxymethylene diphosphonate (HMDP), that have not been previously examined in the literature.…”
mentioning
confidence: 86%
“…Oka et al investigated the potential of 18 F-fluciclovine to aid visualization of bone metastases by comparing the performance of 14 C-fluciclovine with that of 3 H-FDG, 3 H-choline and 99m Tc-hydroxymethylene diphosphonate (HMDP) using triple-tracer autoradiography in rat models of osteolytic bone metastases (derived from breast cancer) and osteoblastic bone metastases (derived from prostate cancer) (32). Histological verification confirmed that 14 C-fluciclovine accumulated in areas of metastatic invasion in both the osteoclastic and the osteoblastic models.…”
Section: F-fluciclovinementioning
confidence: 99%
“…Preclinical studies have demonstrated substantial success of 18 F-fluciclovine in the detection of osseous metastases. 44,45 Physiologic fluciclovine avidity is seen in the liver, pancreas, and skeletal muscle. The physiologic avidity in the liver will likely limit detection of hepatic metastases, a common site of metastatic disease in patients with breast cancer.…”
Section: Basics Of Amino Acid Metabolism In Normal Cells and Malignancymentioning
confidence: 99%